Oxygen radical-scavenging capacities of peptides from swine blood - Jun Fang; Rao Li-qun; Tian Yun; Xiangyang Lu; Hongmei Jiang (African Journal of Pig Farming, 2013)
In China, about five hundred million swine are slaughtered yearly, which represents about 45% of the world´s production. Swine blood is generally discarded except for the small amount that is used in soybean curd and other food products. This not only wastes resources, but also contaminates the environment. In this study, we found that peptides from swine blood had molecular masses of less than 2,100 Da and most were about 1,000 Da. Furthermore, the contents of Glu, Val, Met, Ile, Leu, Phe and Lys were higher than those in dried swine blood. Peptides from swine blood most strongly scavenged ·OH among different oxygen species. This is the first reported study on the oxygen radical-scavenging capacities of peptides from swine blood, and the results suggest that swine blood may be promising for use in food or feed.